Calculus of variations: 21.7. bis 27.7.1974 - Heinz, Erhard; Hildebrandt, Stefan; Jäger, Willi (Tagungsbericht, 1974)
. W. Alt, Münster; W. Alt, Münster; U. Ambrosio, Campina; J. Bemelmans, Bonn; R. Böhme, Göttingen; R. Finn, Bonn Stanford; J. Frehse, Bonn; C. Gerhard, Paris; M. Giaquinta, Pisa; E. Giusti, L'Aquila; K. Goldhorn, Mainz; K. Gornik, Bonn; F. P. Harth, Bonn; E. Heinz, Göttingen; S. Hildebrandt, Bonn; E. Hölder, Mainz; W. Jäger, Münster; H. Kaul, Bonn; H. Kielhöfer, Stuttgart; R. Landes, Bochum; F. Lewerenz, Göttingen; A. Lichnewsky, Paris; U. Massari, Ferrara; J. C. C. Nitsche, Minneapolis; H. Pecher, Göttingen; L. Pepe, Ferrara; E. Pitts, Harrow; P. Rabinowitz, Madison; H. Ruchert, Münster; E. Sperner, Bonn; F. Tomi, Münster; W. von Wahl, Bochum; K.-O. Widman, Linköping; M. Wiegner, Bochum; B. Winzell, Linköping